2005
DOI: 10.1002/ijc.21296
|View full text |Cite
|
Sign up to set email alerts
|

Coffee consumption and breast cancer risk among BRCA1 and BRCA2 mutation carriers

Abstract: Although there are several plausible biologic mechanisms whereby coffee consumption might influence the risk of breast cancer, epidemiologic evidence is limited. We assessed the association between coffee consumption and breast cancer risk among high-risk women who carry BRCA mutations. We performed a matched case-control analysis on 1,690 women with a BRCA1 or BRCA2 mutation from 40 centers in 4 countries. Average lifetime coffee consumption was estimated via a self-administered questionnaire. Odds ratios (OR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
1
3

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 42 publications
1
42
1
3
Order By: Relevance
“…52 Nkondock et al, reported that women with BRCA1 or BRCA2 mutations who consumed at least 6 cups of coffee per day to have a statistically significant reduction in breast cancer risk (OR 5 0.31, 95% CI 0.13-0.71) compared to BRCA mutation carriers who have never drunk coffee. 53 In conclusion, no substantial association was observed between consumption of caffeinated or decaffeinated coffee and tea and risk of breast cancer for the overall cohort. Higher consumption of caffeine-containing beverages may modestly reduce risk of postmenopausal breast cancer, and this relation needs to be examined further.…”
Section: Discussionmentioning
confidence: 78%
“…52 Nkondock et al, reported that women with BRCA1 or BRCA2 mutations who consumed at least 6 cups of coffee per day to have a statistically significant reduction in breast cancer risk (OR 5 0.31, 95% CI 0.13-0.71) compared to BRCA mutation carriers who have never drunk coffee. 53 In conclusion, no substantial association was observed between consumption of caffeinated or decaffeinated coffee and tea and risk of breast cancer for the overall cohort. Higher consumption of caffeine-containing beverages may modestly reduce risk of postmenopausal breast cancer, and this relation needs to be examined further.…”
Section: Discussionmentioning
confidence: 78%
“…Having consumed coffee before age 35 was associated with a 39% reduction in breast cancer risk in this group of genetically susceptible women, consistent with our previous results (1). The current study is based on a subset of women from this earlier study (1). The CYP1A2 genotype alone did not affect breast cancer risk; however, there was an interaction with a history of coffee consumption.…”
Section: Discussionmentioning
confidence: 99%
“…A common A to C polymorphism at position 163 in the CYP1A2 gene has been associated with decreased enzyme inducibility and enzymatic activity, resulting in the slower metabolism of caffeine (79)(80)(81). Some studies reported that among breast cancer susceptibility gene (BRCA1) mutation carriers, the consumption of caffeinated coffee was associated with a signifi cant reduction in breast cancer risk (82). Another study indicated that CYP1A2 genotype did not affect breast cancer risk.…”
Section: Cyp1a2mentioning
confidence: 99%